Nordic whiteness and migration to the USA
1 online resource
Keywords: This volume explores the complex and contradictory ways in which the cultural, scientific and political myth of whiteness has influenced identities, self-perceptions and the process of integration of Nordic immigrants into multicultural and racially segregated American society in the nineteenth and twentieth centuries. In deploying central insights from whiteness studies, postcolonial feminist and intersectionality theories, it shows that Nordic immigrants - Danes, Swedes, Finns, Norwegians and Smi - contributed to and challenged American racism and white identity. A diverse group of immigrants, they could proclaim themselves hyper-white' and better citizens than anybody else', including Anglo-Saxons, thus taking for granted the racial bias of American citizenship and ownership rights, yet there were also various, unexpected intersections of whiteness with ethnicity, regional belonging, gender, sexuality, and political views. Nordic whiteness', then, was not a monolithic notion in the USA and could be challenged by other identities, which could even turn white Nordic immigrants into marginalised figures. A fascinating study of whiteness and identity among white migrants in the USA, Nordic Whiteness will appeal to scholars of sociology, history and anthropology with interests in Scandinavian studies, migration and diaspora studies and American studies.